Saving the ghost of the mountain : an expedition among snow leopards in Mongolia - Montgomery, Sy.; Bishop, Nic, 1955- (Boston : Houghton Mifflin Books for Children, 2009)
Provides an account of an expedition mounted by the Snow Leopard Trust to the mountains of Mongolia in an effort to learn more about the elusive snow leopard and find ways to keep it from extinction.
Includes index.
School Library Journal starred
Wilson's Children
Wilson's Junior High School
Booklist, September 2009
Horn Book, November 2009
Keywords: Snow leopard -- Mongolia -- Juvenile literature; Snow leopard -- Mongolia; Snow leopards